Biological Active Cobalt(II) and Nickel(II) Complexes of 12-Membered Hexaaza [N6] Macrocyclic Ligand Synthetic and Spectroscopic Aspects. Issue 4 (2010) - Kumar, Umendra; Chandra, Sulekh
Abstract : New cobalt(II) and nickel(II) complexes of 12-membered macrocyclic Schiff - base ligand containing thiosemicarbazone moiety as a part of ring have been prepared having general composition [MLX2 ] where M = Co(II) or Ni(II), L=3, 4, 9, 10–tetra-2-furanyl-1, 2, 5, 6, 8, 11- hexaazacyclododeca-7, 12- dithione - 2, 4, 8, 10 – tetraene, X = Cl -, NO3 -, NCS - . The complexes have been characterized by elemental analysis, molar conductance, magnetic susceptibility measurements, spectral (IR, electronic, EPR) techniques and thermal analysis. Spectroscopic studies suggested a six coordinated octahedral geometry for all the complexes. The IR spectra of complexes suggest that ligand is coordinated to the metal ion through its four imines nitrogen. Conductivity measurements supported the non electrolytic nature of the complexes. The antifungal activities of complexes have been studied against a number of pathogenic fungi under laboratory conditions. The complexes showed good antifungal results. Thermal analysis of reported complexes suggests the absence of water molecule either in or outside the coordination sphere.